1997
DOI: 10.1007/s001250050745
|View full text |Cite
|
Sign up to set email alerts
|

Renal glucose production and utilization: new aspects in humans

Abstract: Summary According to current textbook wisdom the liver is the exclusive site of glucose production in humans in the postabsorptive state. Although many animal and in vitro data have documented that the kidney is capable of gluconeogenesis, production of glucose by the human kidney in the postabsorptive state has generally been regarded as negligible. This traditional view is based on net balance measurements which, other than after a prolonged fast or during metabolic acidosis, showed no significant net renal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
120
1
12

Year Published

1999
1999
2015
2015

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 233 publications
(134 citation statements)
references
References 78 publications
1
120
1
12
Order By: Relevance
“…We failed to observe any effect of acute insulin deficiency on renal glucose production in type 1 diabetic subjects, but as noted above it is possible that more severe hypoinsulinaemia could have promoted renal glucose production. In particular, it should be noticed that under the current conditions insulin withdrawal did not augment circulating epinephrine concentrations and that epinephrine has been reported to stimulate renal glucose production; and blood levels of epinephrine increase in severe diabetic derangement, such as ketoacidosis [4,6]. Table 5 Arterial plasma concentrations and whole-body appearance rates for palmitate and femoral and renal net palmitate balances, and palmitate release and uptake rates in five diabetic subjects with and without insulin and in six control subjects Enhanced lipolysis and uncontrolled ketogenesis following insulin deprivation can lead to diabetic ketoacidosis.…”
Section: Discussionmentioning
confidence: 69%
See 2 more Smart Citations
“…We failed to observe any effect of acute insulin deficiency on renal glucose production in type 1 diabetic subjects, but as noted above it is possible that more severe hypoinsulinaemia could have promoted renal glucose production. In particular, it should be noticed that under the current conditions insulin withdrawal did not augment circulating epinephrine concentrations and that epinephrine has been reported to stimulate renal glucose production; and blood levels of epinephrine increase in severe diabetic derangement, such as ketoacidosis [4,6]. Table 5 Arterial plasma concentrations and whole-body appearance rates for palmitate and femoral and renal net palmitate balances, and palmitate release and uptake rates in five diabetic subjects with and without insulin and in six control subjects Enhanced lipolysis and uncontrolled ketogenesis following insulin deprivation can lead to diabetic ketoacidosis.…”
Section: Discussionmentioning
confidence: 69%
“…The renal contribution to endogenous glucose production has been a matter of much controversy [4][5][6][7][8][9][10][11][12]28]. Much of the confusion in all likelihood has arisen from the fact that measurements across the renal bed, because of the high renal blood flow of around 1 l/min, are highly susceptible to methodological imprecision as regards analysis of differences in arteriovenous glucose concentrations and dilution of tracers.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly moderate increase of insulin suppressed liver, but not kidney, PEPCK mRNA in both the PEPCK transgenic and control rats. As has been previously suggested [32], this implies that kidney PEPCK is not as insulin responsive as liver PEPCK and that increased renal glucose production can be a substantial contributor to glucose turnover [36,37]. It has been shown that in patients undergoing liver transplantation endogenous glucose production falls about 50% after removal of the liver, representing renal glucose production [38].…”
Section: Discussionmentioning
confidence: 91%
“…Accumulation of cadmium in both liver and kidney is a cause for concern as these two organs contribute to the maintenance of blood glucose levels (Gerich 2010;DeFronzo et al 2012). In the post absorptive state, kidney and liver supply an equal amount of glucose into blood circulation (Stumvoll et al 1997;Gerich 2010;DeFronzo et al 2012). Further, cadmium accumulation in kidney and RPE could contribute to early onset of diabetic nephropathy and retinopathy as seen in the Torres Strait (Australia) population who had elevated dietary cadmium exposures (Satarug et al 2000b;HaswellElkins et al 2007a,b;Haswell-Elkins et al 2008).…”
Section: Salient Features Of Cadmiummentioning
confidence: 99%